Modelación de un prototipo rehabilitador de muñecas para personas con discapacidad motriz. - Sailema Sailema, Eliza Verónica (2021)
The objective of this research is the characterization of a rehabilitative electromechanical prototype, which contributes to the medical sciences in the recovery physical motor through active therapies that are applied to patients who suffer from This type of disability is either congenital or acquired. For the CAD computer-aided design process, SolidWorks software is used, where the modeling of the mechanism of the phalanges of the five fingers of the hand is elaborated, taking into account the anthropometry of the human body, the impression is made through additive manufacturing or CAM computer-aided manufacturing using the material called PLA polylatic acid for its mechanical properties, such as the rigidity of excellent structural resistance in the prototype, the electronic phase is programmed in the language of the Arduino Mega 2560 represented in the programming flowchart , and the electrical system is applied by means of 6V direct current motors with a ratio of 1 to 75, with a reduction box which are housed in each finger in charge of generating the extension and flexion movements of the fingers of the hand. The flexion movements oscillate from ±100° to 105° and the extension movements oscillate from 0° to 45°, through the tests it is obtained as a result of the flexion 104.8° and the extension of 0.7° complying with the parameters established for its correct operation. Regarding the line of research: design, construction and maintenance of elements, prototypes and electromechanical systems, it provides technical solutions to the problem in the health-oriented rehabilitation process.